Sabah women cruise into semifinals - Bingkasan, Lester J. (Borneo Post (KK), 2016)
KOTA KINABALU: Sabah women team booked their semifinal spot in the 29th Tun Sharifah Rodziah Football Tournament after a 9-0 trouncing of Perlis in Sintok, Kedah yesterday.